LICENSING E-MONEY INSTITUTIONS IN THE EUROPEAN UNION AS A WAY OF TRANSFERRING GLOBAL CAPITAL FLOWS - Слобода, Лариса (Socio-economic relations in the digital society, 2020)
This research consists of a general analysis of the benefits and requirements to obtain the e-money institution license in the European Union countries. The author outlines the main analytical trends and regulatory issues for providing remittances by European payment institutions. An analysis of the digital remittance transactions conducted by the e-money service providers in the EU shows a positive tendency of the value is expected to show an annual growth rate (CAGR 2020—2023) of 13.1% resulting in the total amount of USD 59,774m by 2023. The conclusion clarifies opportunities for investors which may use this way for transferring global capital flows across the EU in other world countries for parking and safeguarding their money for the initial phase of the global financial crisis 2020. Case studies provide market-valuable insights about the value of remittances in the different countries in the EU, compare advantages for the licensing e-money institutions against commercial banks, and present descriptions of the requirements and key stages of the application process to be undertaken for payment institutions in the European financial market.